Dinamika Komunikasi Islam dalam Membangun Relasi dengan Organisasi Politik pada Era AI (Artificial Intelligence) di Indonesia - Pardianto, Pardianto (Journal of Management, Education and Communication, 2026)
This article aims to analyze the dynamics of Islamic communication in building relationships with political organizations in the age of AI. This study employs a qualitative research method using a literature review approach, examining various academic sources such as books, scholarly journals, and related publications. Research findings indicate that Islamic communication is undergoing a transformation characterized by the digitization of da’wah, the use of algorithms in message dissemination, the role of social media as a space for interaction between religious and political actors, the digitization of political da’wah, and the expansion of religious authorities’ reach in the digital age, which strengthens the political participation of Muslims. On the other hand, challenges such as polarization and the echo chamber effect have emerged. Therefore, it is necessary to strengthen the ethics of Islamic communication based on the values of honesty, responsibility, and information verification (tabayyun) in facing the AI era. The development of AI also has significant implications for democratic practices in Indonesia.